Ultrasonographic evaluation of fetal kidney length as a reliable parameter for estimation of gestation age in 2nd & 3rd trimester - Shaheen, Wafa; Gilani, Syed Amir; Hasan, Zain-ul; Fatima, Mehreen; Bacha, Raham; Malik, Sajid Shaheen (International Journal of Applied Sciences and Biotechnology, 2019)
The fetal Kidney length can be used in estimation of gestational age. In late 2nd and 3rd trimester both kidneys can be visualized easily and can be measured accurately. In late 2nd and 3rd trimester the fetal kidney length can be used as an investigational tool alone or may be in addition of other parameter in estimation of gestational age. The most commonly used parameters used by sonologist can predict gestational age in 1st and 2nd trimester. But as pregnancy advances, the accuracy of these parameters decreased. The length of fetal kidneys in mm collaborates very nicely with gestational age in weeks Objective: To evaluate that fetal kidney length is a reliable parameter for gestational age estimation in 2nd and in 3rd trimester of pregnancy. Methods: 371 healthy, pregnant females with a normal fetus were included in this study. A standard 2nd and 3rd trimester ultrasound examination was done. In addition to the standard biometric parameters, both fetal kidneys length were also measured. The collected data was subjected to statistical analysis. Results: This study finding confirmed that fetal kidney length can be used as standard parameters alone or in addition with other routine parameters for estimation of gestational age in late 2nd and 3rd trimester. The Pearson correlation coefficient r=0.988 which showed a strong correlation with kidney length and gestational age and p value is (0.00) Conclusion: Fetal kidney length estimates gestational age as accurate as other standard traditional parameters. It is more accurate in late 2nd & 3rd trimesters of pregnancy when other parameters are not much reliable. It is easy to detect and measure. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 108-113